Quantitative Three-Dimensional Reconstructions of Excitatory Synaptic Boutons in the "Barrel Field" of the Adult "Reeler" Mouse Somatosensory Neocortex: A Comparative Fine-Scale Electron Microscopic Analysis with the Wild Type Mouse. (9th December 2019) - Prume, Miriam; Rollenhagen, Astrid; Yakoubi, Rachida; Sätzler, Kurt; Lübke, Joachim Hr
Abstract: Synapses are key structural determinants for information processing and computations in the normal and pathologically altered brain. Here, the quantitative morphology of excitatory synaptic boutons in the "reeler" mutant, a model system for various neurological disorders, was investigated and compared with wild-type (WT) mice using high-resolution, fine-scale electron microscopy (EM) and quantitative three-dimensional (3D) models of synaptic boutons. Beside their overall geometry, the shape and size of presynaptic active zones (PreAZs) and postsynaptic densities (PSDs) forming the active zones and the three pools of synaptic vesicles (SVs), namely the readily releasable pool (RRP), the recycling pool (RP), and the resting pool, were quantified. Although the reeler mouse neocortex is severely disturbed, no significant differences were found in most of the structural parameters investigated: the size of boutons (~3 μm 2 ), size of the PreAZs and PSDs (~0.17 μm 2 ), total number of SVs, and SVs within a perimeter (p) of 10 nm and p20 nm RRP; the p60 nm, p100 nm, and p60–p200 nm RP; and the resting pool, except the synaptic cleft width. Taken together, the synaptic organization and structural composition of synaptic boutons in the reeler neocortex remain comparably "normal" and may thus contribute to a "correct" wiring of neurons within the reeler cortical network.